Pediatric dermatofibrosarcoma protuberans: A clinicopathologic and genetic analysis of 66 cases in the largest institution in Southwest China - Zhang, Zhang; Lu, Yang; Shi, Changle; Chen, Min; He, Xin; Zhang, Hongying (Frontiers in Oncology, 2023)
Background Dermatofibrosarcoma protuberans (DFSP) is an uncommon cutaneous tumor in children. Most published articles are sporadic or small series and lack systematically molecular analyses. The aim of our study is to better understand the clinicopathologic and genetic features of these rare lesions. Methods All patients diagnosed with DFSP aged ≤ 18 years were retrospectively reviewed from January 2006 to May 2022. Results A total of 66 cases (32 male and 34 female patients) were identified, with ages ranging from 0.3 to 18 years (median, 13 years). Tumor locations predominantly occurred on the trunk (38/66, 57.6%), followed by the extremities (20/66, 30.3%) and head/neck (8/66, 12.1%). Histological findings revealed classic (41/66, 62.1%), myxoid (4/66, 6.1%), pigmented (6/66, 9.1%), plaque-like (3/66, 4.5%), giant cell fibroblastoma (GCF; 6/66, 9.1%), and fibrosarcomatous (6/66, 9.1%) variants of DFSP. Immunochemistry revealed minority tumors (9/66, 13.6%) showing patchy or negative staining for CD34. Fluorescence in situ hybridization (FISH) indicated that 49 of 53 tested cases including all detected biopsy specimens (11/11) contained COL1A1-PDGFB fusion, in which the average copy number gain of COL1A1-PDGFB was 0.68. There were four cases negative for COL1A1-PDGFB rearrangement, one of which was found to harbor a novel COL3A1-PDGFB fusion by next-generation sequencing (NGS). Treatment for 63 patients comprised 40 marginal excisions and 23 wide local excisions (WLEs), including 1 with imatinib therapy. Follow-up information was available on 49 patients with a duration of 12–161 months (median, 60 months). Fourteen patients developed tumor recurrence, all with initial marginal excisions. The others survived with no evidence of disease. Conclusions This study of pediatric DFSP indicates certain discrepancies in clinicopathologic characteristics between children and adults. The majority of pediatric DFSPs contain COL1A1-PDGFB fusion, the same as their adult counterparts. The COL3A1-PDGFB chimerism might be associated with the special morphology of GCF, which needs further investigation. FISH is valuable in biopsy tissues and cases with atypical CD34 immunostaining, while supplementary NGS could be helpful to identify the cytogenetically cryptic DFSP. Overall, an urgent accurate diagnosis is needed to formulate an optimal therapeutic strategy in the pediatric population.